Biochemical evidence for two different gene pools in lima beans, Phaseolus lunatus L - Debouck, Daniel G.; Maquet, A.; Posso G, Carmen Elisa (1989)
A total of 96 accessions (82 cultivated and 14 wild) of lima beans, Phaseolus lunatus, from CIAT`s collection, were analyzed for their seed`s CP composition. So far, 2 major families of electrophoretic patterns can be distinguished in the cultivated materials, showing that they come from 2 different groups of wild ancestors: one of Meso American origin (from Jalisco (Mexico) to Salta (Argentina)) and the 2nd from the Andes, present in Cajamarca (Peru). An intermediate pattern was also found in a wild form in Panama (G25818). Results indicate that P. lunatus is a single species with 2 independent sets of genes; however, more studies should be conducted with greater samples to understand the problem of small-seeded lima bean. (CIAT)